The Miocene lacustrine carbonate factory of the Ñirihuau Formation, Ñirihuau Basin, North Patagonian Andes, Argentina - Santonja, Camila (2024)
Facies, microfacies and stable isotope analyses of limestone beds in the northernmost Ñirihuau Basin, North Patagonian Andes, Argentina, document and constrain the past hydrological, sedimentological and climate conditions that prevailed during the deposition of a lacustrine system between ca 15 and 13 Ma. This palaeoenvironment is recorded in the middle section of the Ñirihuau Formation, which holds significance because: (1) It was deposited during a transition from an extensional to a compressional tectonic regime; (2) it spans the Middle Miocene Climatic Optimum and the beginning of the Middle Miocene Climatic Transition; and (3) it contains limestone beds interbedded within a 600 m thick interval of mudstones and siltstones, along with intercalated sandstone and volcaniclastic bodies. Two detailed sedimentary logs were surveyed along the Arroyo Las Bayas, at the western and eastern flank of the David Syncline. Limestones from both stratigraphic sections were sampled as well as isolated limestone beds from two other sites. One facies association was defined and interpreted as a perennial lake associated with a deltaic system and dominated by detrital clastic material. It comprises Facies 1 (Marginal lacustrine) and Facies 2 (Lower delta plain); in both, the presence of grainstones and calcimudstones stands out. Through petrography and cathodoluminescence studies of these continental carbonates, nine microfacies were identified: (a) Intraclastic grainstone, (b) Homogeneous calcimudstone, (c) Silty grainstone, (d) Disrupted micrite, (e) Birds eye micrite, (f) Bioclastic mudstone, (g) Calcimudstone with sparse detrital grains, (h) Fenestral micrite, (i) Stromatolitic boundstone. These indicate mainly bio-induced subaqueous carbonate precipitation and subordinate deposition by tractive flows with short-distance transport on a littoral lacustrine environment. Most of these microfacies exhibit very early diagenesis (eogenesis) effects. These features, and the geochemistry results, indicate that they were deposited in a palaeolake system under temperate to warm and humid conditions.